Middle-late Miocene normal faulting in the intermontane Tarom basin during the collisional deformation of the Arabia-Eurasia collision zone, NW Iran: A regional process or a local feature?. (1st September 2021) - Paknia, Mohammad; Ballato, Paolo; Heidarzadeh, Ghasem; Cifelli, Francesca; Oskooi, Behrooz; Feinberg, Joshua; Jackson, Mike; Bilardello, Dario; Salvini, Francesco; Mirzaie Ataabadi, Majid; Tadayon, Meisam; Reza Ghassemi, Mohammad; et al.
Graphical abstract: Highlights: Magnetic fabric in the central Tarom Basin records NE-SW layer parallel shortening. Magnetic fabric in the SW margin of the basin is a primary sedimentary fabric. NE-SW orogen-perpendicular syndepositional extension occurs in the SW margin. Normal faults in the SW margin were induced by gravity instabilities. Middle-late Miocene extension is not regionally pervasive. Abstract: The upper plate of the Arabia-Eurasia collision zone experienced orogen-perpendicular to orogen-parallel extension from 25–22 to 10–9 Ma. Although such an extension occurred during widespread collisional deformation, it is not clear if it is a local feature or if represents a major phase of upper plate extension. In this study we combine anisotropy of magnetic susceptibility (AMS) with fault kinematic analysis and sedimentologic data from 16.2- to 7.6-My-old deposits of the Upper Red Formation of the intermontane Tarom Basin (NW Iran). These strata present syndepositional, normal faults and offer the possibility to gain new insights into the spatial extent of such a Miocene extension. AMS data from the central and northern sectors of the basin document a tectonic fabric with a magnetic lineation parallel to the strike of the orogen, suggesting a compressional tectonic overprint. Conversely, the southern margin of the basin presents a purely sedimentary magnetic fabric despite a ~NE–SW orogen-perpendicular extension. This suggests that basin formation was not driven by extensional tectonics. Rather, the normal faults are gravity instabilities induced as also documented by coeval landslide deposits. This allows concluding that the orogen-perpendicular extension observed in few sectors of the collision zone is not regionally pervasive and hence it is not controlled by large-scale processes. Combined, our results indicate that if orogen-parallel extension associated with tectonic denudation and metamorphic core complex development occurred in certain sectors of the collision zone (Takab complex), it must have ended before 19–16 Ma, when widespread upper plate contractional deformation started.